Social Sustainability in Selecting Emerging Economy Suppliers - Ehrgott, Matthias (Journal of business ethics, 2011)
Despite the growing public awareness of social sustainability issues, little is known about what drives firms to emphasize social criteria in their supplier management practices and what the precise benefits of such efforts are. This is especially true for relationships with international suppliers from the world’s emerging economies in Asia, Latin America, and Eastern Europe. Building on stakeholder theory, we address the issue by examining how pressures from customers, the government, and employees as primary constituencies of the firm determine the extent to which firms consider social aspects in the selection of emerging economy suppliers. Further, we analyze how such socially sustainable supplier selection relates to the capabilities of the firm’s suppliers, its market reputation, and the learning in its supply management organization. We test the developed research framework empirically using data from 244 U.S. and German corporations. Our findings, consistent with our hypothesized model, suggest that middle-level supply managers as internal stakeholders play a major driving role for firms’ socially sustainable supplier selection, and that strong positive links exist between that selection and the investigated outcomes.